Pharmacokinetics of Once-Daily Darunavir/Ritonavir With and Without Etravirine in Human Immunodeficiency Virus-Infected Children, Adolescents, and Young Adults. (28th January 2015) - Larson, Kajal B.; Cressey, Tim R.; Yogev, Ram; Wiznia, Andrew; Hazra, Rohan; Jean-Philippe, Patrick; Graham, Bobbie; Gonzalez, Amy; Britto, Paula; Carey, Vincent J.; Acosta, Edward P.
Abstract: Background: Limited data are available for once-daily (QD) darunavir (DRV)/ritonavir (r) in the pediatric population. Coadministration of etravirine (ETR) may alter the pharmacokinetics (PK) of DRV. We evaluated the PK interactions between DRV/r (QD) and ETR QD or twice-daily (BID) in children, adolescents, and young adults. Methods: Human immunodeficiency virus-infected subjects 9 to < 24 years old on optimized background therapy including DRV/r 800/100 mg QD alone or combined with ETR 200 mg BID or ETR 400 mg QD were enrolled. Protocol-defined target drug exposure ranges based on adult data were used to assess the adequacy of each regimen. Intensive 24-hour blood sampling was performed, and PK parameters were determined using noncompartmental analysis. Results: Thirty-one subjects (14 males) completed the study; 16 received DRV/r QD alone (group 1), 6 received DRV/r plus ETR BID (group 2A), and 9 received DRV/r plus ETR QD (group 2B). The geometric mean (90% confidence interval [CI] geometric mean) for DRV area under the curve at 24 hours (AUC 24 ) was 57.9 (49.6–67.6), 74.9 (44.4–126.5), and 66.4 (50.8–86.9) mg × h/L for patients in groups 1, 2A, and 2B, respectively. The increased DRV exposure when coadministered with ETR was not statistically significant. The geometric mean (90% CI geometric mean) of ETR AUC 24 was 8.6 (4.4–16.8) and 11.9 (7.5–18.9) mg × h/L for groups 2A and 2B, respectively, with comparable C 24 . Conclusions: The results suggest that DRV/r QD with ETR 400 mg QD or 200 mg BID is appropriate and support further evaluation of the safety and efficacy of the once-daily regimen in older children, adolescents, and young adults.